Intestinal Langerhans cell histiocytosis presenting with symptoms similar to inflammatory bowel disease: a case report - Yuqing Liu; Zhenwei Chen; Lu Wang; Baizhou Li (Pathology and Oncology Research, 2024)
Background:Langerhans cell histiocytosis is a rare disease characterized by the abnormal proliferation of Langerhans cells within a single organ or multiple organs. This case report aims to improve the knowledge of the presentation of gastrointestinal Langerhans cell histiocytosis to facilitate the diagnosis and management of this rare disorder.Case presentation:A 19-month-old female presented with repeatedly mucinous bloody stools. The abdominal ultrasound revealed a slightly enlarged spleen. The initial colonoscopy revealed chronic enteritis with a very early onset inflammatory bowel disease. After anti-inflammatory treatment without improvement, an intestinal biopsy was performed at The Forth Affiliated Hospital of Zhejiang University. The final intestinal biopsy and histopathology examination confirmed the presence of Langerhans cell histiocytosis. After diagnosis, additional lung and head imaging examinations revealed no abnormalities. Her condition improved gradually after being treated with chemotherapy (vincristine and prednisone) and molecular-targeted drug(dalafinil) treatment.Conclusion:The clinical symptoms of Langerhans cell histiocytosis involving the gastrointestinal tract are not specific and may resemble symptoms observed in inflammatory bowel disease and other primary gastrointestinal tumors. Therefore, in cases of infants presenting with inflammatory gastrointestinal symptoms that do not resolve after treatment, a biopsy is essential to obtain a differential diagnosis.